2020
DOI: 10.1001/jamaneurol.2019.3446
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Parkinson Disease in Bipolar Disorder

Abstract: ipolar disorder (BD) is a mood disorder that has an early onset at a median age of 20 years. It is a long-term and recurrent disorder characterized by cyclic episodes of depression and either mania (BD type 1) or hypomania (BD type 2). Although the etiology of BD has not been established, it is a multifactorial disorder with genetic and environmental factors playing an important role. 1 Despite the pathophysiology of BD being uncertain, there is a putative role of the dopaminergic system, as levodopa has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 23 publications
11
50
0
2
Order By: Relevance
“…Interestingly, we note that there was a male preponderance in our BD population. Since PD is more common in men (41), we cannot exclude that gender might also play a role in the development of degenerative parkinsonism in BD, an issue that has not been carefully examined in the previous studies (4,30) and deserves future ad hoc investigations, further considering possible different clinical profiles of BD between men and women (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we note that there was a male preponderance in our BD population. Since PD is more common in men (41), we cannot exclude that gender might also play a role in the development of degenerative parkinsonism in BD, an issue that has not been carefully examined in the previous studies (4,30) and deserves future ad hoc investigations, further considering possible different clinical profiles of BD between men and women (42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has suggested that BD would be associated with later development of PD, with a 3-fold higher risk than the general population (4). However, a subgroup analysis showed a greater likelihood of PD diagnosis in studies with shorter followup, suggesting a possible misdiagnosis of PD (4). BD treatment includes lithium, antipsychotics, and antiepileptic drugs (AEDs), all of which can cause drug-induced parkinsonism (DIP) (5); thus, overestimation of the presence of PD in BD could have been possible since the individual studies included in the meta-analysis might not have differentiated PD from DIP (6).…”
Section: Introductionmentioning
confidence: 99%
“…All together the review and meta‐analysis suggest that patients with BD have a significantly increased risk of developing PD compared with the general population …”
mentioning
confidence: 96%
“…It is usually attributed to side effects of medication, but can also be a result of concomitant cerebrovascular disease and even an emerging idiopathic Parkinson's disease (PD). In a recent meta‐analysis by Faustino et al published in JAMA Neurology, the association of BD with a later diagnosis of PD was assessed . Four cohort studies and three cross‐sectional studies reporting data on the likelihood of developing PD in BD vs non‐BD populations were included, with a total of 4.374.211 participants overall.…”
mentioning
confidence: 99%
“…EPS are linked to lower treatment adherence, poorer psychiatric prognosis and increased mortality ( 1 , 2 ) and are more severe and frequent in patients with SMI than in other psychiatric disorders, with higher prevalence (68–74%) among hospitalized patients ( 3 , 4 ). Patients with bipolar disorder are particularly likely to develop Parkinson's Disease (PD) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%